2018
DOI: 10.1099/ijsem.0.002540
|View full text |Cite
|
Sign up to set email alerts
|

Mixta gen. nov., a new genus in the Erwiniaceae

Abstract: The Erwiniaceae contain many species of agricultural and clinical importance. Although relationships among most of the genera in this family are relatively well resolved, the phylogenetic placement of several taxa remains ambiguous. In this study, we aimed to address these uncertainties by using a combination of phylogenetic and genomic approaches. Our multilocus sequence analysis and genome-based maximum-likelihood phylogenies revealed that the arsenate-reducing strain IMH and plant-associated strain ATCC 700… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…Because these strains were classified prior to the description of the proposed Mixta calida , we considered the single M . calida strain found in our study to be correctly identified [38]. Three non- Pantoea strains, 07–703, 12BT205805, and B012497 are sufficiently divergent that they remain unclassified.…”
Section: Discussionmentioning
confidence: 53%
“…Because these strains were classified prior to the description of the proposed Mixta calida , we considered the single M . calida strain found in our study to be correctly identified [38]. Three non- Pantoea strains, 07–703, 12BT205805, and B012497 are sufficiently divergent that they remain unclassified.…”
Section: Discussionmentioning
confidence: 53%
“…Previously, P. citrea , P. terrea , and P. punctata were transferred to the genus Tatumella (Brady et al, 2010). Recently, Pantoea calida , Pantoea gaviniae , Pantoea theicola , and Pantoea intestinalis were moved to a new genus Mixta (Palmer et al, 2018). This suggests that the taxonomy of the genus is evolving probably due to the use of improved taxonomic methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…The genera Coetzeea and Thorsellia, are the only genera described for the Thorselliaceae family. Even though this review focuses only on genera within the family Enterobacteriaceae described during the 21th century, Table 1 shows all the families and genera that belong to the order Enterobacteriales [13][14][15][16][17][18][19][20][21] , in order to show the genera related to Enterobacteriaceae.…”
Section: Resultsmentioning
confidence: 99%